Realization of 2D (2,2)-periodic encoders by means of 2D periodic separable Roesser models - Napp, Diego; Pereira, Ricardo; Pinto, Raquel; Rocha, Paula (Zielona Góra: Uniwersytet Zielonogórski)
in the implementation of convolutional codes is to obtain a minimal state representation of the code. Compared with the literature on one-dimensional (1D) time-invariant convolutional codes, there exist relatively few results on the realization problem for time-varying 1D convolutional codes and even fewer if the convolutional codes are two-dimensional (2D).
Keywords: periodic 2D systems; convolutional codes; realizations